Artificial intelligence in the public sector: progress versus regress? - Viktorija Girinskienė (Taikomieji Moksliniai Tyrimai)
AI is analysed from different perspectives, one of which is the application of AI in the public sector. The development of the AI requires a responsible approach, including ethical guidelines, regulation, and continuous public education. It is important to strike a balance between promoting innovation and minimising potential negative consequences. There is also a need to promote technology development in a way that benefits society as a whole and not just certain groups. It is becoming a common tool in education. Already, AI is changing the way schools, universities, students, and educators work and children learn. Educational institutions benefit from it by helping teachers meet the specific needs of each learner. There is a strong push for closer cooperation on digital education at European Union level and the importance of collaboration across all sectors to make education fit for the digital age. The article provides a general overview of artificial intelligence, its impact on society, how it can be applied in the public sector, whether humans are already able to exploit and benefit from this technology, and how to guard against the negative effects of technology. What legal measures need to be taken to ensure that artificial intelligence is a progress for mankind and not a regression in any field.